Model Pendidikan Profetik Bagi Orang Tua Dalam Mendidik Anak - Wahyu Ningsih; Ahmad Munawar; Sherly Ananda (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
This research discusses the application of the prophetic education model as a guide for parents in shaping children's character and morals. By referring to the teachings of the Prophet Muhammad SAW, this research identifies values ​​such as justice, compassion and patience as the core of prophetic education. Through literature analysis and case study methods, this research explores how the Prophet Muhammad SAW provided a real example in educating children. This model emphasizes the importance of providing positive role models, effective communication, and developing social skills in the family environment. The research results show that the application of the prophetic education model can help parents shape their children's personalities holistically. The practical implications of this research can contribute to the development of family education programs based on prophetic values, so as to create the next generation with strong character and noble morals.